Perceptual link between inadequate water, sanitation, and hygiene (WASH) stressors and common mental symptoms in Ethiopian health workers: A qualitative study - Yitagesu Habtu; Abera Kumie; Medhine Selamu; Hidenori Harada; Morie Kaneko; Mirgissa Kaba; Eshetu Girma (PLoS ONE, 2025)
Background Despite the rising prevalence of common mental symptoms, information is scarce on how health workers make sense of symptoms of mental disorders and perceive a link with inadequate water, sanitation, and hygiene (WASH) as work stressors to understand causation and produce useful knowledge for policy and professionals. Therefore, this study aimed to explore how health workers perceive the link between inadequate WASH and common mental symptoms (CMSs) at hospitals in central and southern Ethiopian regions. Methods We used an interpretive and descriptive phenomenological design guided by theoretical frameworks. Three focus group discussions (FGDs) and 10 in-depth interviews with health workers were conducted. We explored the perceived link with inadequate WASH after assessing health workers’ conceptualization of common mental health symptoms. The interviews and FGDs were audio recorded, transcribed, and translated into English. Coding and categorizing were supported by MaxQDA software 2020. Thematic analysis was performed and themes were supported by participants’ quotes when necessary. Results Four themes emerged from the data based on the guiding theoretical models relevant to the research questions. Most health workers believed and frequently suggested that inadequate water supply, functional hand hygiene, environmental cleaning, and waste management services at the points of care increased the risk of occupational stress, job anxiety, and occupational depression symptoms. Many participants believed that inadequate WASH would cause them to experience negative professional quality of life including burnout, compassion dissatisfaction, and compassion fatigue at work despite believing that WASH problems cannot be solved at the individual level. Participants recurrently listed many individual, organizational, and system-level barriers to reducing and coping with inadequate WASH as stressors. Conclusions Healthcare workers perceived inadequate WASH components as contributing to symptoms of common mental disorders and negatively impacting their professional quality of life. They faced multiple barriers at individual, organizational, and health system levels, which hindered their ability to manage work-related stress and seek mental health support. The findings suggest the implementation of integrated WASH and mental health services for healthcare workers, ranging from establishing individual-level interventions to increasing access to WASH around care areas through collaborative efforts with healthcare administration, broader health systems, water supplies, and sewerage services.